Teaching the Students and not the Book: Addressing the Problem of Culture Teaching in EFL in Argentina (GIST – Education and Learning Research Journal, 2012)
The aim of this study was to discover teachers' attitudes towards culture in the EFL classroom in three different institutions in La Plata, Argentina. In order to do this, eleven EFL teachers who were using three different EFL textbooks (World English 3, Laser B1+, and Upstream B2+) were interviewed using a semi-structured questionnaire. Also, with the aim of determining to what extent these textsbooks reflect "the global coursebook" and whether they address Argentine students' cultural needs, a content analysis using an a priori approach was carried out. The results showed that these textbooks tend to deal with and to avoid the same topics and that they are not identity enhancers for local students. As for teachers' attitudes towards culture teaching, the results also indicate that teachers hardly notice this problem and do very little to remedy it.